Кодированные маски для рентгеновских и гамма-телескопов - Содин, Л.Г. (Кинематика и физика небесных тел, 1995)
Предложен новый способ синтеза кодированных масок, используемых в качестве входных апертур телескопов рентгеновского и гамма-диапазонов. Метод снимает ограничения на свободу выбора важнейших параметров, таких как чувствительность и разрешающая способность. Пропонується новий метод синтезу кодованих масок, які використовуються як вхідні апертури телескопів рентгенівського та гамма-діапазонів. Метод знімає обмеження на свободу вибору найважливіших параметрів, таких як чутливість і роздільна здатність. A new method for the synthesis of coded masks used as input apertures for X-ray and gamma-ray telescopes has been suggested. The method avoids restrictions on the freedom of a choice of some important parameters such as sensitivity and resolution because the possibility has been found to synthesize coded masks (both rectangular and square) of practically any dimensions.